Use of Herbicides in Sugarcane in the São Paulo State - REIS,F.C. (2019)
ABSTRACT: Sugarcane is one of the main agricultural cultivations of Brazil, and one of the crops in which herbicides are most applied. In the 2017/2018 season, the estimated sugarcane production was 694.54 million tons, with an estimated increase of 0.9% in yield for this season. In order to evaluate the use of herbicides in this crop in the São Paulo State during a five-year period, a survey was carried out with sugarcane farmers. The use of herbicides applied alone and in a formulated mixture, according to their mechanism of action, were evaluated from 2010 to 2014. Photosystem II inhibitor herbicides were the most used in this period and the total amount of herbicides of almost all mechanism of action increased from 2010 to 2014, except for photosystem I inhibitors herbicides. The use of formulated mixtures also increased during this period. The area treated with carotenoid biosynthesis and photosystem II inhibitor herbicides was the largest for the control of monocotyledonous species (Poaceae, Cyperaceae and Commelinaceae). In relation to the dicotyledonous species, the area treated with PROTOX inhibitor herbicides was the largest in all evaluated years.